2019
DOI: 10.1002/chem.201901874
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Air‐stable, Odorless Thiophenol Surrogates via Ni‐Catalyzed C−S Cross‐Coupling

Abstract: Thiophenols are versatile synthetic intermediates whose practical appeal is marred by their air sensitivity,t oxicity and extreme malodor.H erein we report an efficient catalytic method for the preparation of S-aryl isothiouronium salts, and demonstrate that these air-stable, odorless solids serve as user-friendly sources of thiophenols in synthesis. Diverse isothiouroniums alts featuring synthetically useful functionality are readily accessible by nickel-catalyzed CÀS cross-coupling of (hetero)aryl iodides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The construction of the C-S bond is one the most significant transformations in modern organic synthesis, as molecules containing the C-S bond are mostly found in abundance in biomolecules, pharmaceutical drugs, 104 dyes 105 and many more significant materials. Drugs like vortioxetine 106,107 (antidepressant), sertaconazole 108 (anti-fungal) and organic semiconductors like BTBT, DNT 109 are also important sulphur-containing compounds. Conventional methods for C-S bond construction include dehydrogenative coupling, oxidative/photoredox-catalysed tandem cyclization and pre-functionalization.…”
Section: C-s Bond Formationmentioning
confidence: 99%
“…The construction of the C-S bond is one the most significant transformations in modern organic synthesis, as molecules containing the C-S bond are mostly found in abundance in biomolecules, pharmaceutical drugs, 104 dyes 105 and many more significant materials. Drugs like vortioxetine 106,107 (antidepressant), sertaconazole 108 (anti-fungal) and organic semiconductors like BTBT, DNT 109 are also important sulphur-containing compounds. Conventional methods for C-S bond construction include dehydrogenative coupling, oxidative/photoredox-catalysed tandem cyclization and pre-functionalization.…”
Section: C-s Bond Formationmentioning
confidence: 99%
“…The formation of the C–S bond is also an important transformation in organic synthesis applications, especially as a method to rapidly increase the complexity of molecules to be used in biomedicine and materials science. 10 Therefore, efforts at searching for efficient methods that enable rapid construction of these structures are still highly appreciated. 11 One of the most conventional methods used for constructing quinoline compounds containing sulfide groups is based on the transition-metal-catalyzed cross-coupling reactions of quinoline halides or of those bearing other leaving groups with thiols/thiophenols (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…In seeking to address these manifold challenges, we recently reported a convenient and scalable method for the synthesis of S-aryl isothiouronium salts, which serve as airstable, odorless surrogates to thiophenols (Scheme 1). 6 Inspired by the work of Takagi, 7 we showed that Ni-catalyzed C-S coupling of thiourea and diverse (hetero)aryl iodides proceeds under mild, base-free conditions to afford the cor-Scheme 1 Air-stable, odorless S-aryl isothiouronium salts are readily accessible via Ni-catalyzed C-S cross-coupling/precipitation and serve as convenient surrogates for thiophenols in synthesis. 6 DNB: 3,5-dinitrobenzoate.…”
mentioning
confidence: 99%
“…6 Inspired by the work of Takagi, 7 we showed that Ni-catalyzed C-S coupling of thiourea and diverse (hetero)aryl iodides proceeds under mild, base-free conditions to afford the cor-Scheme 1 Air-stable, odorless S-aryl isothiouronium salts are readily accessible via Ni-catalyzed C-S cross-coupling/precipitation and serve as convenient surrogates for thiophenols in synthesis. 6 DNB: 3,5-dinitrobenzoate. es 16 that could interfere with the proposed mechanism of Miyake's S-arylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation